Millenial Youth Assistance in an Effort to Increase Arabic Terms Knowledge towards Sharia Banking Product Contracts - Adinugraha, Hendri Hermawan; Mashudi, Mashudi; Mubtadi, Novendi Arkham (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
The formulation of the problem raised in this study is how the application of semiotization to Islamic banking products among millennial teenagers who incidentally are customers and prospective customers of Islamic banking?, and what are the results after semiotics are educated and socialized to them?. The purpose of this service is to educate how to easily understand Arabic terms in Islamic banking product contracts using the semiotic method among millennial youth who are in fact customers and prospective customers of Islamic banking. The method used in this service is education, outreach, and mentoring to millennial youth regarding Arabic terms on Islamic banking product contracts as an effort to increase knowledge of Arabic terms on Islamic banking product contracts. The findings of this dedication are expected to provide academic contributions and increase scientific hazanah in the field of innovation in understanding Islamic banking products using semiotization so that it is easily understood by the general public, especially by customers and prospective customers of Islamic banking millennial youth, and can be used as a reference or reference for academics and academics, general public.